Delineation of potential groundwater zones in the Kagna river basin of Gulburga district, Karnataka, India using remote sensing and GIS techniques (MAUSAM, 2008)
The potential groundwater zones in parts of Kagna river basin of Gulburga district, Karnataka, have been delineated on the basis of geomorphic units alongwith geological setting, lineaments indicating bore well locations using remote sensing and GIS. The study area covers an area of 1318 sq km and it is divided into Wadi, Chitapur, Sedam and Kurkunta sub-basins which range in area from 184 to 537 sq km.  Lithologically, the area consists of basement gneisses with granites overlain by conglomerate, sandstone, shale and limestone with a thin cover of Deccan basalts.  Hydrogeomorphologically, the entire area is classified into escarpment slope, pediments, pediment inselberg complex, shallow pediplains, moderate pediplains, slightly to highly dissected and undissected plateaus, valleys and shallow valley fills. The lineaments representing drainages and dykes are oriented in NNW, NW, EW and NE directions. Most of boreholes are located nearer to the lineaments indicating that the lineaments are acting as pathways for the movement of groundwater. Based on lineament and hydrogeomorphic analysis, it is suggested that the valley fills and moderate pediplains are very good to good, shallow pediplains and dissected plateau are good to moderate, pediments are moderate to poor and the pediment inselburg complex and escarpment slope are the poor to very poor potential groundwater zones.